Latin America in Light of China’s Global Economic Power: Brazil and Ecuador and their foreign policies. A Comparative Study - Herrera-Vinelli, Lorena (2017)
This article aims to outline the factors that have influenced the strengthening of Sino-Latin American relations. It argues that Latin America’s political, commercial and financial interests towards China are explained in terms of the position consolidated by China as the world’s second largest economy. An analysis of Brazil as a relatively industrialized country and of Ecuador as a small nation serve as an empirical reference in explaining and understanding how the foreign policies of both countries have behaved with respect to China and allows us to question the priority areas of their relationship from a comparative perspective. The article concludes that while both countries have a strategic relationship with China, in Brazil’s case, foreign policy is strongly tied to China in the political, commercial and financial spheres, while Ecuador's financial dependence on China is the most important element in its foreign policy.